Tuberkulóza v Ceské republice a ve svete - Krejbich, F; Homolka, J; Svobodová, L (Casopis lekaru ceskych, 2007)
Tuberculosis is a general infectious inflammatory disease caused by the bacillus (mycobacterium) tuberculosis. The disease originated when the bacillus was transmitted from affected cattle herds to humans. Genetic methods proved the existence of tuberculosis in mummies of the ancient Egypt. In the 19th and 20th century socio-economic conditions enabled pandemics of tuberculosis. The essential element for spreading of tuberculosis is the tuberculous patient. The disease develops in 10% of those who were infected. Tuberculosis manifests by long-lasting coughing, night sweating, tiredness, growing slim, febriles and loss of appetite. Diagnosis can be established on the basis of thoracic sciagram, confirmed by microscopic and cultivation examination of sputum. In the Czech Republic, an effective surveillance of tuberculosis was established with resulting good epidemiological situation.
Keywords: plicní tuberkulóza; Tuberculosis, Pulmonary; lidé; Humans